Analysis of yeast conservative nucleotide sequences by genomic bioinformatic methods - Yarmolenko, Marianna; Zelena, Lyubov; Hretsky, Igor; Tkachuk, Nataliia (Problems of Environmental Biotechnology, 2021)
The purpose of the present study was the bioinformatic analysis of conservative nucleotide sequences, their variability between different yeast species and genus. The results obtained in the study can facilitate the selection of yeast phylogenetic biomarkers and promote the establishment of yeast sequences database.